Peranan komitmen keselamatan sebagai pengantara dalam hubungan amalan pengurusan keselamatan dan pengetahuan keselamatan dengan inisiatif keselamatan - Mazliah, Abdul Rahman (2020)
The previous literature review rarely discusses specific safety initiatives towards paddy farmers in the agricultural sector. Furthermore, the dimensions describing safety initiatives were not detailed. Safety initiatives are proactive behaviors to enhance safety in the workplace. However, in the case of an incident, paddy farmers are not protected by the Social Security Act 1969. In this regard, the objectives of this study are to develop the dimensions of safety initiatives and to determine the role of safety commitment among paddy farmers as mediating the relationship between safety management practices and safety knowledge with safety initiatives. Cross- sectional studies using the theory of planned behavior (TPB) have been conducted on paddy farmers in Peninsular Malaysia by using disproportionate stratified random sampling. A total of 745 questionnaires were received and analyzed from farmers under the supervision of the Department of Agriculture, KADA, MADA, KETARA, IADA, and FELCRA. Quantitatif data were analyzed descriptively and interentially by Statistical Package for Social Science (SPSS) version 20.0. The results show that the seven hypotheses have a significant impact on safety commitment and safety initiatives. The finding also indicates that safety commitment can act as a mediator in the relationships between safety management practices and safety knowledge with safety initiatives. In addition, factor analysis found that two factors that explain the dimensions of safety initiatives. These two dimensions are known as safety responsibility and safety alert. Finally, this study discusses the theoretical and practical implications as well as suggestions for future research.